THE EFFECT OF INSTITUTIONAL OWNERSHIP AND BOARD CHARACTERISTICS ON EARNINGS MANAGEMENT - Estu Widarwati; Vidia Apriliani (STIESA Press, 2024)
This study is based on institutional ownership. The existence of institutional ownership in a company is considered to be an effective monitoring tool in every decision taken by management. Institutional ownership will encourage increased monitoring to optimize management performance. This study aims to test the effect of institutional ownership and board characteristics on earnings management. In measuring institutional ownership (X1) using institutional ownership. Board characteristics measurement uses two proxies, namely board age and number of board meetings (X2), then earnings management measurement (Y) uses discretionary accruals, and leverage measurement (C) uses Debt on Assets Ratio (DAR). The sample used in this study were 12 consumer goods industry companies with sub-sectors of food and beverage, pharmaceutical, cigarette, cosmetics and household goods industries listed on the IDX in 2021-2023 and there were 36 observations. The study uses panel data regression analysis by applying Eviews12. The sampling technique used in determining the sample uses purposive sampling. Data collection techniques use literature studies and documentation. The results of this study indicate that institutional ownership has no effect on earnings management. For testing board characteristics proxied using board age, it has no significant effect on earnings management, while testing board characteristics proxied using the number of board meetings has a significant effect on earnings management. For testing leverage, it has no significant effect on earnings management. Thus, the findings of this research have implications that companies must implement institutional ownership to increase more optimal monitoring of management performance. So it can reduce management's desire to carry out earnings management.